Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To determine the quotient of \( \frac{20 \sqrt{z^6}}{\sqrt{16 z^7}} \) in simplest radical form, follow these steps:
1. Simplify the numerator:
[tex]\[ 20 \sqrt{z^6} \][/tex]
Since \( \sqrt{z^6} = z^3 \), the numerator becomes:
[tex]\[ 20 z^3 \][/tex]
2. Simplify the denominator:
[tex]\[ \sqrt{16 z^7} \][/tex]
Recognize that \( 16 = 4^2 \) and \( z^7 = z^6 \times z \). Therefore, we can rewrite the expression under the square root as:
[tex]\[ \sqrt{16 z^7} = \sqrt{(4^2) (z^6 \times z)} = \sqrt{(4^2 z^6) \cdot z} = 4 \sqrt{z^6 \cdot z} \][/tex]
Given \( \sqrt{z^6 \cdot z} = \sqrt{z^7} = z^{7/2} \), the denominator simplifies to:
[tex]\[ 4 z^{7/2} \][/tex]
3. Form the quotient:
[tex]\[ \frac{20 z^3}{4 z^{7/2}} \][/tex]
4. Simplify the coefficient:
[tex]\[ \frac{20}{4} = 5 \][/tex]
Hence, the expression becomes:
[tex]\[ \frac{5 z^3}{z^{7/2}} \][/tex]
5. Simplify the expression with exponents:
Recall that \(z^3 = z^{6/2}\). Rewrite the expression as:
[tex]\[ \frac{5 z^{6/2}}{z^{7/2}} \][/tex]
Subtract the exponents:
[tex]\[ 5 z^{(6/2 - 7/2)} = 5 z^{-1/2} = 5 \cdot \frac{1}{z^{1/2}} \][/tex]
6. Rationalize the expression:
Recall that \( \frac{1}{z^{1/2}} = \frac{1}{\sqrt{z}} \), so we get:
[tex]\[ 5 \cdot \frac{1}{\sqrt{z}} = \frac{5}{\sqrt{z}} \][/tex]
Therefore, the quotient of \( 20 \sqrt{z^6} \div \sqrt{16 z^7} \) in simplest radical form is:
[tex]\[ \boxed{\frac{5}{\sqrt{z}}} \][/tex]
1. Simplify the numerator:
[tex]\[ 20 \sqrt{z^6} \][/tex]
Since \( \sqrt{z^6} = z^3 \), the numerator becomes:
[tex]\[ 20 z^3 \][/tex]
2. Simplify the denominator:
[tex]\[ \sqrt{16 z^7} \][/tex]
Recognize that \( 16 = 4^2 \) and \( z^7 = z^6 \times z \). Therefore, we can rewrite the expression under the square root as:
[tex]\[ \sqrt{16 z^7} = \sqrt{(4^2) (z^6 \times z)} = \sqrt{(4^2 z^6) \cdot z} = 4 \sqrt{z^6 \cdot z} \][/tex]
Given \( \sqrt{z^6 \cdot z} = \sqrt{z^7} = z^{7/2} \), the denominator simplifies to:
[tex]\[ 4 z^{7/2} \][/tex]
3. Form the quotient:
[tex]\[ \frac{20 z^3}{4 z^{7/2}} \][/tex]
4. Simplify the coefficient:
[tex]\[ \frac{20}{4} = 5 \][/tex]
Hence, the expression becomes:
[tex]\[ \frac{5 z^3}{z^{7/2}} \][/tex]
5. Simplify the expression with exponents:
Recall that \(z^3 = z^{6/2}\). Rewrite the expression as:
[tex]\[ \frac{5 z^{6/2}}{z^{7/2}} \][/tex]
Subtract the exponents:
[tex]\[ 5 z^{(6/2 - 7/2)} = 5 z^{-1/2} = 5 \cdot \frac{1}{z^{1/2}} \][/tex]
6. Rationalize the expression:
Recall that \( \frac{1}{z^{1/2}} = \frac{1}{\sqrt{z}} \), so we get:
[tex]\[ 5 \cdot \frac{1}{\sqrt{z}} = \frac{5}{\sqrt{z}} \][/tex]
Therefore, the quotient of \( 20 \sqrt{z^6} \div \sqrt{16 z^7} \) in simplest radical form is:
[tex]\[ \boxed{\frac{5}{\sqrt{z}}} \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.